Reconstruction Of Lower Lip By Neurovascular Fan Flap - Khan, Dr. Masood H.; Khan, Dr. Arshad H.; Yaseen, Dr. M. (Indian Journal of Plastic Surgery, 1992)
Full thickness excisional defects of upper and lower lips are normally reconstructed by local tissues such as remaining lip segment. And adjacent check tissues, whenever possible or by regional or distant flaps when defects are large.Disadvantages inherited in all these flaps are loss of continuity of oral sphincter because of interruption of orbiculari oris muscle continuity and aesthetical unsatisfactory results. In present case a technique is used where above factors are overcome.
Keywords: Full thickness Defect